The Embedded U-Suture Technique for Better Cosmetic View in Patients Underwent Endoscopic Thoracic Sympathectomy - Muhammet Sayan; Irmak Akarsu; Muhammet Tarık Arslan; Ayşegül Kurtoğlu; Günel Ahmedova; Ali Çelik (Gazi Medical Journal, 2025)
In endoscopic thoracic sympathectomy (ETS) surgery, a chest drain is inserted into the pleural space after the procedure for lung expansion and is quickly removed after lung hyperinflation. A horizontal mattress suture, also named U-suture, is quickly knotted around the chest drain to prevent air from entering the pleural space. The U-suture may cause poor cosmetic appearance because of excessive scar tissue development. In this study, we aimed to investigate the new embedded U-suture technique using polyglactin suture, which is an absorbable material, and its cosmetic results. In this retrospective study, we collected data on patients who underwent ETS performed with a new technique. A total of 30 patients were included in the study. Neither serious wound complications nor excessive scar formation was observed in the follow-ups of the patients. The embedded U-suture technique in ETS surgery has some advantages such as good cosmetic results, no need for the removal of sutures, and applicability in both genders.